CagA mediates epigenetic regulation to attenuate let-7 expression in Helicobacter pylori-related carcinogenesis. Issue 11 (30th August 2012) - Hayashi, Yoshito; Tsujii, Masahiko; Wang, Jun; Kondo, Jumpei; Akasaka, Tomofumi; Jin, Ying; Li, Wei; Nakamura, Toru; Nishida, Tsutomu; Iijima, Hideki; Tsuji, Shingo; Kawano, Sunao; et al.
Abstract : Objective: MicroRNAs (miRNAs) act as tumour suppressor genes or oncogenes in the regulation of multiple carcinogenic processes. Aberrant miRNA expression is reported in Helicobacter pylori ( H pylori )-related gastritis and gastric cancer. The cytotoxin-associated gene A (CagA) of H pylori has a pathophysiologically important role in gastric carcinogenesis. A study was undertaken to evaluate the effect of CagA on miRNA expression and its regulatory mechanism. Methods: The effect of CagA on miRNA expression was assessed by comprehensive miRNA microarray. The mechanisms of the in vitro and in vivo effects of CagA on histone modification and DNA methylation and the involvement of CagA-dysregulated signal transduction on let-7, an important representative miRNA in gastric carcinogenesis, were investigated. Results: In in vitro experiments, CagA significantly attenuated let-7 expression leading to Ras pathway activation. CagA enhanced c-myc, DNA methyltransferase 3B (DNMT3B) and Enhancer of Zeste homologue 2 (EZH2) expression and attenuated miR-26a and miR-101 expression, which resulted in the attenuation of let-7 expression by histone and DNA methylation. Experiments performed in CagA transgenic mice revealed that c-myc, EZH2 and DNMT3B expression were enhanced and let-7 expression was attenuated to induce Ras oncoprotein expression in the stomach, with no associated inflammation. Conclusions: H pylori CagA induces aberrant epigenetic silencing of let-7 expression, leading to Ras upregulation.